Adaptive-Psychological Learning Framework: Redefining Human Nature and Methodology in the Digital Era - Andi Najamuddin; Mansur Mansur; Fatmawati Fatmawati; Baso Syafaruddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The growing digitalization of education has accelerated the mechanization of learning, frequently marginalizing the psychological dimensions of human nature. Prevailing methodologies prioritize narrow cognitive outcomes while neglecting autonomy, affective engagement, and the social essence of learners, resulting in diminished meaning and learner well-being. This study critically analyzes the philosophical and practical implications of human nature—as conceptualized in behaviorism, cognitivism, and humanistic psychology—for the transformation of learning methodologies in contemporary educational contexts. A qualitative library research design was employed, drawing on systematic searches of Scopus, ScienceDirect, and Google Scholar. Content analysis and thematic synthesis were applied to 28 peer-reviewed sources published between 2000 and 2023, with theoretical triangulation used to ensure rigor. Three complementary psychological pillars were identified: behaviorism’s contribution to structured feedback, cognitivism’s emphasis on scaffolded mental construction, and humanism’s prioritization of autonomy and self-actualization. Synthesis of these pillars yields an Adaptive-Psychological Methodology (APM) framework. Additionally, the concept of Digital Humanism is proposed, repositioning technology as an amplifier of human agency rather than a substitute for it. Student psychological well-being is argued to constitute a primary indicator of educational success, superseding exclusive reliance on cognitive achievement metrics. Meaningful educational transformation requires a paradigm shift from mechanistic, teacher-centered instruction toward human-centered, facilitative methodologies grounded in psychological science. The three-stage Reorientation–Reconstruction–Resonance (3R) strategic framework is offered as a practical guide for educators, curriculum designers, and policymakers.